Eye movements reveal sexually dimorphic deficits in children with fetal alcohol spectrum disorder - Paolozza, Angelina; Munn, Rebecca; Munoz, Douglas P.; Reynolds, James N. (Frontiers in Neuroscience, 2015)
Background: We examined the accuracy and characteristics of saccadic eye movements in children with fetal alcohol spectrum disorder (FASD) compared with typically developing control children. Previous studies have found that children with FASD produce saccades that are quantifiably different from controls. Additionally, animal studies have found sex-based differences for behavioral effects after prenatal alcohol exposure. Therefore, we hypothesized that eye movement measures will show sexually dimorphic results. Methods: Children (aged 5-18 years) with FASD (n=71) and typically developing controls (n=113) performed a visually-guided saccade task. Saccade metrics and behavior were analyzed for sex and group differences. Results: Female control participants had greater amplitude saccades than control males or females with FASD. Accuracy was significantly poorer in the FASD group, especially in males, which introduced significantly greater variability in the data. Therefore, we conducted additional analyses including only those trials in which the first saccade successfully reached the target within a ±1˚ window. In this restricted amplitude dataset, the females with FASD made saccades with significantly lower velocity and longer duration, whereas the males with FASD did not differ from the control group. Additionally, the mean and peak deceleration were selectively decreased in the females with FASD. Conclusions: These data support the hypothesis that children with FASD exhibit specific deficits in eye movement control and sensory-motor integration associated with cerebellar and/or brain stem circuits. Moreover, prenatal alcohol exposure may have a sexually dimorphic impact on eye movement metrics, with males and females exhibiting differential patterns of deficit.